Musical Training in the Development of Empathy and Prosocial Behaviors - Wu, Xiao; Lu, Xuejing (Frontiers in Psychology, 2021)
Music not only regulates mood but also promotes the development and maintenance of empathy and social understanding. Since empathy is crucial for well-being and indispensable in social life, it is necessary to develop training strategies to improve empathy and prosocial behaviors. To fulfill this aim, researchers have extensively investigated the effect of intensive musical training on the development of empathy. Here we first summarize evidence showing the powerful influence of musical training on the development of empathy and then discuss psychological mechanisms responsible for those observations. The conclusions drawn from most previous studies were mainly based on behavioral measurements, while the neural basis of musical training in the development of the empathic brain is still unclear. Fortunately, brain imaging research has contributed greatly to our understanding of the neural underpinnings associated with musical training and its possible connection to the development of the empathic brain. One of the most distinctive signatures of musical training is structural and functional changes of multiple brain regions, and such changes might be related to some of the empathic behaviors observed in musically trained children. Therefore, intensive musical training in childhood may increase levels of empathy, and applied research is required to optimize the training strategy before implementing music education in empathy regulation. Moreover, future longitudinal studies are needed to better understand neural mechanisms underlying the causal effect of musical training on empathy development. These findings have important implications for understanding the development of the empathic brain and for improving prosocial behaviors.